Sum code family formation method with undetectable error minimum in data vectors - D. V. Efanov; V. V. Sapozhnikov; Vl. V. Sapozhnikov (Informatika, 2019)
The research results of the methods for formation of separable sum codes with the minimum number of undetectable errors in data vectors are presented. A formula for counting the number of undetectable errors in data vectors and codes family properties are given. A universal method for formation of such codes is shown, which makes it possible for each value of the data vector length to obtain a whole family of codes that also have different distributions of undetectable errors by type and multiplicity. An example of codes formation, methods for analyzing characteristics, code comparison are presented. A method for synthesizing coders of developed sum codes is suggested.